2009
DOI: 10.1021/la901601z
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Alkanedithiols on Au(111) from Solution: Effect of Chain Length and Self-Assembly Conditions

Abstract: A comparative study on the adsorption of buthanedithiol (BDT), hexanedithiol (HDT), and nonanedithiol (NDT) on Au(111) from ethanolic and n-hexane solutions and two different preparation procedures is presented. SAM characterization is based on reflection-absorption infrared spectroscopy, electrochemistry, X-ray photoelectron spectroscopy, and time of flight direct recoil spectroscopy. Results indicate that one can obtain a standing-up phase of dithiols and that the amount of the precursor lying-down phase dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
106
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 53 publications
12
106
0
Order By: Relevance
“…[9] They reach this conclusion by measuring the ratio of the S2p core level shift at 163.5 eV related to free S-H bonds or disulfides and 162 eV related to thiolates. Interestingly, by monitoring the 163.5 eV peak, they conclude that the signal comes from terminal sulfur atoms that have formed disulfide bridges.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[9] They reach this conclusion by measuring the ratio of the S2p core level shift at 163.5 eV related to free S-H bonds or disulfides and 162 eV related to thiolates. Interestingly, by monitoring the 163.5 eV peak, they conclude that the signal comes from terminal sulfur atoms that have formed disulfide bridges.…”
Section: Resultsmentioning
confidence: 97%
“…In a previous study, it has been shown that BDT SAM formation leads to a mix of standing-up and flat-lying phases, contrary to NDT which leads to disulfides formation. [9] And thus, the disulfides formation is lower for BDT compare to NDT. This weaker tendency of BDT for forming rows can be explained by the shorter chain length and by the weaker van der Waals interactions between the alkyl chains in neighbouring molecules [33].…”
Section: Resultsmentioning
confidence: 99%
“…Thiol terminal of the DSP binds to the Au surface and a biochemical recognition element with an NH 2 -terminal can be instantly immobilized, since succinimide group of DSP is replaced by amines in a neutral buffer in a single step. However, since alkanethiols with short alkyl chains are often shown to adopt a lying-down phase [25,26], the orientation of biochemical recognition element can significantly affect the sensitivity of the biosensor. We will, therefore, discuss the relationship between the sensitivity of the sensor and the lying-down configuration of the molecules in domain structure.…”
Section: Introductionmentioning
confidence: 99%
“…The chain length and the preparation procedure in the surface structure and chemistry of SAMs of DTs on Au(1 1 1) have been regarded as important features recently [16,17]. In these studies, it is inferred that the best way to prepare DT SAMs is by using n-hexane N 2 saturated solutions in absence of light.…”
Section: Introductionmentioning
confidence: 99%